Prevalência de alergia alimentar em pré-escolares das escolas municipais de Educação Infantil de Uberlândia/MG - Guimarães, Tássia Cecília Pereira (2014)
Food allergy is an adverse health effect arising in any immune response that occurs reproducibly on an exposure to a given food. This allergy has shown significant increase in recent decades, with a prevalence estimated around 6-8% in the pediatric age group. Although the most frequent element that causes food allergy is cow milk, allergies triggered by soy, egg, fish, peanuts, wheat, corn, rice and seafood are also possible. The estimated range of self-reported food allergy prevalence is from 3% to 35%. Therefore, this study intends to know the prevalence of reported food allergy diagnosed by parents and that prevalence diagnosed health professionals, as well as major food and clinical manifestations in preschool children enrolled in municipal daycare centers from Uberlândia, Minas Gerais, Brazil. Concerning the methods, it is an epidemiological study in children from 24 to 59 months who were enrolled in municipal daycare centers from Uberlândia, with a self-administered questionnaire that was used to evaluate the prevalence of food allergy related by parents; subsequently, children with a suspecting food allergy were invited to a clinical and laboratory evaluation, in order to know the real prevalence of food allergy. According to the results, from 13,841 children enrolled, 8,031 parents responded the questionnaire. The prevalence of food allergy reported by parents was 17.6%, and the incidence of asthma, rhinitis and dermatitis was significantly higher in the group of children with reported food allergy (p = < 0.0001). The main foods mentioned were cow milk, pork, fruit, chocolate and chicken egg, and associated symptoms were red spots (54.2%), vomit (39.6%), diarrhea (32.1%), abdominal pain (31.4%), mouth and eyes edema (17.5%) and nose secretion (10.6%). The prevalence of food allergy was in 0.59% of preschool children, which 0.35% had IgE -mediated reactions and 0.24% non- IgE mediated reactions. The egg was the main food allergen, reaching 0.34% of preschool children, followed by cow milk (0.21%), wheat and pork meat (0.06%), corn, mustard, honey and fish (0.03%). The main symptoms were red spots and itching (52.6%), diarrhea (42%), eyes edema and abdominal pain (36.8%). It was concluded that the prevalence of food allergy reported by parents and confirmed food allergy prevalence are similar to those found in the literature, showing a strong association with allergic diseases (asthma, atopic dermatitis and allergic rhinitis). The main foods reported by parents confirm the eating habits from the researched area. Several studies have reported that regional and cultural influences interfere on the food allergens types. Thus, most of the foods associated with food allergy in this study such as milk, egg, wheat, corn, fish, pork meat, mustard and honey were described in the world literature. A significant number of children excluded food allergen without a medical diagnosis of food allergy.